PERBEDAAN RESPON KECEMASAN ANAK USIA PRASEKOLAH DAN ANAK USIA SEKOLAH TERHADAP TINDAKAN PENGAMBILAN DARAH - , MONIKA JUVENTIANA V F; , Elsi Dwi Hapsari, S.Kp., M.S., D.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
development in preschoolers and school-aged children indicates the differences of anxiety between preschoolers and school-aged children. Objective: This study aimed to determine differences in anxiety responses of preschoolers and school-age children to the procedure of blood taking Methods: It was non-experiment with obeservational design. The study was conducted in Poliklinik Anak (Pediatric Policlinic) and Laboratorium Anak (Pediatric Laboratory) RSUP Dr.Sardjito between May â June 2013. As many as 30 preschoolers and 30 school-aged children participated in this study. Observation sheet made by researcher based on Hitijahubessyâs observation sheet (2006). Two observers were used to observe the anxiety response (agreement = 0,952). Mann Whitney test was used to analyse the data Result : Anxiety response in preschoolers was significantly highers than in school-aged children (8,5 vs 2,87, p=0,000). Motoric and physiologic anxiety response in preschoolers also highers than in school-aged children (6,37 vs 1,63, p = 0,000